Plant-parasitic nematode population in tropical forages in 2 altitude range of San Carlos County, Alajuela - WingChing-Jones, Rodolfo (2010)
Plant-parasitic nematode populations in Black sorghum grass (Sorghum almus), Cameroon grass (Pennisetum purpureum var Camerun), King grass (Pennisetum purpureum var King grass), Tanzania grass (Panicum maximum var Tanzania), Brizantha grass (Brachiaria brizantha), Toledo grass (Brachiaria brizantha var Toledo), African star grass (Cynodon nlemfuensis), Mombaza grass (Panicum maximum var Mombaza), Smutgrass (Ischaemum ciliare) and perennial peanut legume(Arachis pintoi) were characterized during June to November 2003 at San Carlos, Alajuela. Five compound samples of roots and associated soil of with grazing forages were taken, except for King grass, Smutgrass and peanut legume, where the number of samples was 10 for each forage. The nematodes Pratylenchus sp., Helicotylenchus sp., Tylenchus sp., and Criconemella sp., were identified in 8 forages and the perennial peanut legume. Psilenchus sp., was present only in Tanzania grass, while Xiphinema sp., was found in Tanzania grass, Brizantha grass, Smutgrass and perennial peanut legume. Paratylenchus sp., was recorded in Tanzania grass, Brizantha grass and Smutgrass. Hemicycliophora sp., was observed in Toledo grass, Cameroon grass and perennial peanut legume; Meloidogyne sp,. was found in Brizantha grass and Smurtgrass. Non plant parasitic nematodes were identified in the perennial peanut legume and all 9 forages evaluated.